Use of metal-free carbon materials for converting plastics to c2-C4 olefins and / or hydrocarbons under direct induction heating and method thereof
Through the combination of metal-free carbon materials and direct induction heating, the problems of low efficiency and fast catalyst deactivation in the prior art are solved, and a highly efficient, selective and energy-saving plastic conversion process is achieved.
Patent Information
- Application Number
- CN202380066657.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-09
- Filing Date
- 2023-08-25
- Publication Date
- 2025-05-06
AI Technical Summary
The prior art has problems of low efficiency, fast catalyst deactivation and high energy consumption in converting plastics into low-carbon olefins, and traditional heating methods lead to uneven heat, affecting process selectivity.
Using a combination of metal-free carbon materials with direct induction heating, the plastic is directly converted to low carbon olefins, especially ethylene and propylene, or to other hydrocarbons, such as liquid hydrocarbons and gaseous C1 to C5 alkanes.
An efficient, selective and energy-saving plastic conversion process is achieved, which avoids the problems of catalyst deactivation and heat inhomogeneity, and reduces production costs and environmental impacts.
Smart Images

Figure CN119948132A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the use of materials to convert plastics into C2-C4 olefins and / or other hydrocarbons, and methods for converting plastics into C2-C4 olefins or other hydrocarbons.
[0002] Therefore, the present invention has utility in the field of plastics and chemical industries, especially in the field of recycling.
[0003] In the following description, references in brackets ([ ]) refer to the reference list located at the end of the text. Background Art
[0004] Plastic is one of the main commodities used daily in almost all fields, from industrial packaging to healthcare and composite materials for transportation and storage. It is estimated that about 380 million tons of petroleum-based plastics were produced in 2015. Most of it is used for packaging (mainly single-use), while the rest is used in construction, automobiles, electrical equipment and many other applications. Considering the annual growth rate, it is also estimated that this number is expected to double by 2035. Single-use plastics (40%) as daily necessities are one of the main sources of carbon dioxide, causing environmental and health problems, because currently about 90% of waste plastics are discarded or landfilled, and only a small amount is recycled. In addition, a large part of waste plastics ends up in rivers and oceans, causing problems for the natural environment.
[0005] New legislation and environmental initiatives have greatly contributed to the increase in waste plastic recycling to produce raw materials for new plastics or liquid fuels for transportation and petrochemical industries. Plastic-to-fuel (PTF) has attracted increasing academic and industrial interest since last year. Recently, several announcements have been made by different industries for new plants to convert waste plastics into valuable gaseous / liquid components, which has helped to increase the renewable benefits of such processes.
[0006] Plastic waste is itself contaminated by other products, so before starting the recycling process, it is necessary to carry out preliminary sorting and cleaning. Nowadays, different recycling methods are available, depending on the quality and purity of plastic waste: (i) reuse (direct use of waste plastic), (ii) reprocessing or mechanical recycling, (iii) depolymerization into monomer raw materials (not for all types of waste plastic), (iv) conversion of waste plastic into hydrocarbon raw materials and finally (v) energy recovery through incineration. The recycling efficiency also depends on the nature of the various additives present in the plastic.
[0007] The conversion of plastics into liquid or gaseous hydrocarbons can also recover solid waste components that cannot be reused or recovered by mechanical or depolymerization methods and avoid landfill or incineration. Compared with incineration, waste plastic recycling can significantly reduce greenhouse gas (GHG) emissions. In addition to converting waste plastics into liquid fuels, other research has also focused on converting such wastes into light olefins, which are extremely useful for building blocks chemicals (i.e., raw monomers for plastic production). However, the direct conversion of waste plastics into light olefins is not a simple process, so indirect routes have been developed by converting waste plastics into intermediate hydrocarbons and further converting these chemicals into light olefins. Onwudili et al. (Onwudili et al., 2019 ([1])) studied the conversion of polyolefin vapors from a mixture of plastics (HDPE, LDPE, PP, PS and PET) using Y-zeolite at 500°C and ZSM-5 zeolite at 600°C via FCC (fluid catalytic cracking). The amount of C2-C4 olefins obtained was relatively low, about 21 wt%.
[0008] The depolymerization of polyolefins into their monomer components, i.e., the plastic-to-olefin (PTO) process, requires relatively harsh pyrolysis conditions and produces a complex hydrocarbon mixture. Generally speaking, polyolefins are pyrolyzed at a temperature of ≤500°C to produce carbon chain lengths in the range of C 10 -C 40 range of paraffin mixtures, while more aromatics are produced under more severe conditions, and finally olefin-rich gases and char are produced under even more severe conditions (≥700°C) (Lopez et al., 2017 ([2]); Dogu et al., 2021 ([3])). In order to maximize the olefin component, the aliphatic compounds produced under mild conditions can be further processed into lower olefins by a steam cracker (FCC), which can produce 65 wt% olefin yield. Synova technology is based on the use of a hot fluidized sand bath to crack plastic waste to produce liquids and tars, which are further cracked to obtain olefin-rich gases. Anellotech and BioBTX have developed pyrolysis technology using acidic zeolites to convert plastic pyrolysis vapors into lower olefins and waxes. However, catalyst deactivation requires complex reactor design and frequent catalyst regeneration (J.-P. Lange, Managing Plastic Waste-Sorting, Recycling, Disposal, and Product Redesign, ACSSustain. Chem. Eng., 2021, 9, 15722-15738 https: / / doi.org / 10.1021 / acssuschemeng.1c05013 ([4])).
[0009] Furthermore, in order to reduce GHG emissions from the chemical industry, it is highly desirable to replace the usual catalytic process operation mode, i.e., a combination of large gas burners and metal catalysts, with completely new approaches. Since the past few years, there has been great industrial interest in replacing natural gas burners with electric heating systems. For example, a consortium that recently reorganized several oil industry companies has developed new steam crackers that operate by electricity (Layritz et al., 2021 ([5])), electrocatalysis (Schiffer et al., 2017 ([6])), or by using intermediate heating modes of electricity (e.g., microwave, plasma or induction heating) (Jie et al., 2020 ([7]); Zhou et al., 2021 ([8])). It is also desirable to reduce production costs and environmental impact (waste catalyst recovery or disposal) by replacing traditional supported metal or zeolite catalysts with metal-free catalysts. Last but not least, the ability to produce chemicals directly or indirectly using electricity also represents a smart way to store excess electricity from renewable energy sources, which helps to improve energy harvesting from solar and wind power.
[0010] Induction heating (IH) is widely used in the manufacture of industrial metal workpieces (bonding, welding, sintering) in several industries. Heat is generated directly inside the target material, thus significantly reducing the energy lost to conduction or thermal radiation (Wang et al., 2019 ([9])). In these processes, heat can be directed within the target area without excessively heating the entire bulk volume of the furnace. For catalytic processes, it can avoid the thermal decomposition of reactants and products to form undesirable amorphous carbon or by-products. Recently, the IH mode has been reported as an efficient heating mode for operating catalytic processes with significantly improved performance (Wang et al., 2019 ([9])). In addition to the above advantages, IH is also a green heating method for operating catalytic processes because it can be operated using excess renewable energy (RE) sources instead of using traditional fuel burners to provide heat to the reactor, which helps to reduce the CO2 of the process. Faster heat generation in the system can also reduce energy losses during long startup periods when using traditional indirect heating modes. Rapid cooling of the outlet gaseous effluent due to the targeted heating of IH also significantly reduces process costs by reducing the cooling system at the outlet of the catalytic section.
[0011] The most commonly used catalysts for PTF or PTO (plastic to olefin) are based on acidic zeolites, namely ZSM5, USY, which work by acidic cracking to produce liquid or gaseous hydrocarbons from pyrolyzed polymer vapors. A recent study also pointed out the use of acidic carbon-based catalysts to convert industrial waste plastics into jet fuel (Y. Zhang, D. Duan, H. Lei, E. Villota, R. Ruan. Jet fuel production from waste plastics via catalytic pyrolysis with activated carbons. Appl. Energy 251, 113337 (2019)).
[0012] However, there is a need for an alternative process that is simple to use, highly selective, and energy efficient. The present invention meets these and other needs. Summary of the invention
[0013] Applicants have surprisingly discovered that metal-free carbon materials can be used in PTF and PTO processes.
[0014] More specifically, applicants surprisingly report the use of a combination of metal-free carbon materials and direct induction heating at moderate temperatures to convert plastics (e.g., waste plastics) directly into light olefins, particularly ethylene and propylene, or into other hydrocarbons, such as liquid hydrocarbons, particularly fuel oils, and / or gaseous C1 to C5 paraffins.
[0015] The metal-free carbon materials used in the present invention are particularly advantageous due to their high resistance to deactivation in the presence of impurities contained in plastics (e.g., waste plastics), as well as their low production costs compared to other materials. In addition, due to their chemical inertness, these carbon materials can be advantageously regenerated by chemical treatment to remove deposited impurities.
[0016] Furthermore, the metal-free carbon material is active due to heating via direct induction heating, which opens new avenues for the electrification of recycling processes for plastics such as waste plastics.
[0017] The combination of carbon materials and induction heating has several advantages.
[0018] One of the advantages is that the carbon material can be arranged in a fixed bed structure so that heat is uniformly generated on the outer surface of the reacting carbon by eddy currents generated by the interaction between the metal-free carbon material and the magnetic field. The high thermal conductivity of this carbon material also contributes to high heat transfer within the solid bed, which, combined with the high heating rate, can maintain the bed temperature in the highly endothermic PTF or PTO process. This is very advantageous compared to the heating methods of the prior art, such as microwave (MW) heating. In a fixed bed, the particles are in contact with each other and have high heat absorption near the MW antenna. Therefore, only a small area around the MW antenna is actually heated, which can produce local hot spots and have an adverse effect on the selectivity of the process. In order to disperse the heat throughout the reaction section, fluidization is required to provide a uniform heat distribution. However, the use of a fluidized bed results in excessive energy consumption for moving the material, and also produces fine particles due to catalyst wear, which may affect the integrity of the material.
[0019] Another advantage is that the present invention can be implemented in a two-step process, i.e., plastic pre-cracking (also known as vaporization / liquefaction) in a first-stage reactor, while the plastic vapor / liquid or pre-cracking product is blown to a reaction stage on a solid material heated by IH with an inert gas. Advantageously, the pre-cracking stage produces liquid and / or gaseous products. This two-step process helps control the temperature of the pre-cracking stage and the reaction stage. As shown by the applicant, injection molding and actual industrial waste plastics, including intermediate products of plastic recycling processes, can be used in the PTO or PTF process of the present invention.
[0020] Another advantage is that the pre-cracking step and the reaction temperature can be separated, which allows the reaction temperature to be adjusted to adjust the liquid or light olefin products depending on the downstream application.
[0021] Thus, in a first aspect, the present invention provides the use of a metal-free carbon material for converting plastics into C2-C4 olefins and / or other hydrocarbons under direct induction heating at a temperature of less than or equal to 800°C, preferably less than or equal to 700°C, even preferably less than or equal to 600°C, or strictly less than 600°C, or less than or equal to 550°C, or less than or equal to 500°C, for example from 400 to 600°C, or from 450 to 550°C or from 450 to 500°C.
[0022] In a second aspect, the present invention provides a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising a reaction step of passing through a metal-free carbon material under direct induction heating at a temperature of less than or equal to 800°C, preferably less than or equal to 700°C, even preferably less than or equal to 600°C, or strictly less than 600°C, or less than or equal to 550°C, or less than or equal to 500°C, for example 400 to 600°C, or 450 to 550°C or 450 to 500°C. This step may hereinafter be referred to as the "cracking step".
[0023] "Metal-free carbon material" herein refers to a material that is substantially free of metals or preferably completely free of metals. "Substantially free" means that the material may contain trace impurities, including metals, metal oxides and / or zeolites. For example, based on the total weight of the material, the carbon material may contain less than 3000 ppm (0.3 wt %), less than 2000 ppm, less than 1000 ppm, less than 500 ppm, less than 200 ppm, less than 100 ppm, less than 50 ppm, less than 20 ppm, or even less than 1 ppm of metal.
[0024] "Metal" herein refers to any element that forms a metallic structure under normal conditions and that qualifies as a metal on the periodic table, including alkali metals, alkaline earth metals, transition metals, lanthanides, actinides, and post-transition metals.
[0025] "Carbon material" refers herein to a material that is primarily composed of carbon. For example, the material can be composed of more than 50% by weight of carbon, at least 80% by weight of carbon, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 98% by weight, at least 99% by weight, at least 99.5% by weight, at least 99.9% by weight, or at least 99.99% by weight of carbon. Therefore, the carbon material used herein can include a carbon component and a non-carbon component, as described below.
[0026] "Carbon" or "carbon component" herein refers to a component including graphite, graphene, carbon black, acetylene black, pyrolytic carbon, activated carbon, and any combination thereof. In particular, the carbon portion of the carbon material can be selected from a group including or consisting of graphite, graphene, carbon black, acetylene black, pyrolytic carbon, activated carbon, and any combination thereof.
[0027] The carbon material may also contain non-carbon elements, as long as these elements do not meet the above definition of "metal". The carbon material may contain one or more non-carbon elements or components, for example, selected from Na, K, Si, S, N and O. In particular, the carbon material of the present invention may contain one or more non-carbon elements selected from the group consisting of Na, K, Si, S, N and O and mixtures thereof.
[0028] The inventors demonstrate herein that the use of metal-free carbon materials, particularly carbon materials without additives or promoters, in combination with induction heating, is advantageous for the preparation of C2-C4 olefins, because the metal-free carbon materials exhibit greater resistance to deactivation caused by coating by carbon or coke precursor deposition (as encountered by zeolite-based materials), and have better chemical stability in the presence of organic or inorganic impurities in the processed polymer. Advantageously, due to their high chemical inertness compared to other catalysts or materials, spent carbon-based materials can be regenerated by chemical leaching without significant loss of activity. Advantageously, the metal-free carbon materials can play a role in accelerating the conversion process.
[0029] The present invention is therefore based on the combined use of a metal-free carbon material and induction heating for the preparation of C2-C4 olefins from plastics, such as waste plastics. In particular, the present invention relates to such a combination, wherein the temperature of the induction heating is lower than or equal to 800° C. According to an advantageous embodiment, the present invention relates to such a combination, wherein the metal-free carbon material is arranged in a packed bed. According to an advantageous embodiment, the present invention relates to such a combination, wherein the metal-free carbon material is a rolled carbon felt. These embodiments will be described in more detail below.
[0030] In this application:
[0031] - the expression "between ... and ..." is to be understood as including the limit values;
[0032] - any description, even if described with respect to a specific embodiment, is applicable to and interchangeable with other embodiments of the invention;
[0033] - when an element or component is said to be included in and / or selected from a list of enumerated elements or components, it should be understood that, in the relevant embodiments explicitly contemplated herein, the element or component may also be any of the individual enumerated elements or components, or may also be selected from the group consisting of any two or more of the explicitly enumerated elements or components; any element or component enumerated in a list of elements or components may be omitted from that list; and
[0034] - Any recitation of numerical ranges by endpoints herein includes all values subsumed within that range as well as the endpoints of the range and equivalents thereof.
[0035] In some embodiments, the metal-free carbon material has a BET surface area of at least 0.10 m 2 / g, for example 0.10 to 2000 m 2 / g, 0.20 to 1500m 2 / g, 0.50 to 1000m 2 / g, 1.0 to 900m 2 / g, 4.0 to 400m 2 / g, as determined by ASTM-D-3663 (Standard Test Method for Surface Area of Catalysts and Catalyst Supports, 2020).
[0036] In some other embodiments, the metal-free carbon material has a BET surface area of 0.10 to 30.0 m 2 / g, 0.20 to 20.0m 2 / g, or 0.5 to 6.0m 2 / g, or 1.0 to 3.0m 2 / g, as determined by ASTM-D-3663 (Standard Test Method for Surface Area of Catalysts and Catalyst Supports, 2020).
[0037] Advantageously, there is no technical limit to the maximum BET value. A very high BET value means the presence of micropores that have no specific function but do not interfere with the reaction. In some preferred embodiments, the BET surface area of the metal-free carbon material is as small as possible, for example, less than 30.0 m 2 / g, less than 20m 2 / g, less than 6.0m 2 / g, 8.0m 2 / g or even lower than 6.0m 2 / g. The inventors were surprised to find that the smaller the BET surface area, the less energy is required to heat the metal-free carbon material. Without wishing to be limited by a specific mechanism of action, it is possible that, in this case, the high intrinsic thermal conductivity of the carbon material allows for high heat dissipation within it. It also allows for conversion of products toward C2-C4 olefins. In the case of the PTO process, the results seem to indicate that the external surface area, i.e., the exposed geometric surface, is an important factor in converting plastics into light olefins. Advantageously, the metal-free carbon material is a non-porous or less porous material, i.e., characterized in that there is no pore network or the pore network is very small, so as to have a small specific surface area. In this embodiment, the pore size of the material can be higher than 500nm, higher than 1μm, higher than 3μm, or even greater than 5μm, as determined by ASTM D4284 (Standard Test Method for Pore Volume Distribution of Catalysts and Catalyst Supports by Mercury Intrusion Porosimetry).
[0038] In some embodiments, the geometric structure of the carbon material allows good connection between its primary particles, so the high intrinsic thermal conductivity of the carbon material allows high heat dissipation within its matrix. The geometric surface area of the carbon material can be, for example, greater than or equal to about 1.10 -2 m 2 / g, or greater than or equal to about 1.10 -3 m 2 / g, or preferably greater than or equal to about 1.10 -1 m 2 / g and at most 2m 2 / g. The geometric surface can be determined by any means or methods known to those skilled in the art, for example by X-ray computed tomography (Moncada Quintero et al.: "Investigating mass transfer coefficients in lean methane combustion reaction through the morphological and geometric analysis of structured open cell foam catalysts", Chemical Engineering Science Volume 281, 5 November 2023, 119138 (
[18] )).
[0039] As mentioned above, the present invention can use several forms of carbon. In some preferred embodiments, the carbon material is selected from the group comprising graphite, graphene, carbon black, acetylene black, pyrolytic carbon, activated carbon and any combination thereof or consisting of thereof. As described below, this carbon material can be produced with different sizes and shapes.
[0040] The term "graphite" as used herein refers to a crystalline form of elemental carbon in which atoms are arranged in a hexagonal structure. Graphitic carbon is characterized by an ordered three-dimensional graphite crystal structure consisting of layers of carbon atoms arranged in a hexagonal pattern stacked parallel to each other, as determined by X-ray diffraction. The term graphite as used herein includes natural graphite, i.e., essentially in its geologically existing natural crystalline form, and synthetic graphite, i.e., synthetically prepared or processed graphite. Examples of natural graphite include so-called amorphous (nanocrystalline) graphite, flake graphite, and block graphite. Examples of synthetic graphite include pyrolytic graphite, highly oriented pyrolytic graphite (HOPG), synthetic graphite flakes. Unless further limited, the term "synthetic graphite" as used herein is also intended to include non-expanded graphite.
[0041] The term "graphene" as used herein refers to a polycyclic aromatic molecule in which carbon atoms are covalently bonded in the same plane. The covalently bonded carbon atoms can form a six-membered ring as a repeating unit, and can also include at least one of a five-membered ring and a seven-membered ring. Multi-graphene layers are referred to as graphite in the art. Therefore, graphene can be a single layer, or can also include multilayer graphene stacked on other graphene layers. Typically, the maximum thickness of graphene is about 100 nanometers (nm), particularly about 5nm to about 90nm, more particularly about 20nm to about 80nm. Graphene can also be used in the form of expanded graphite, in which the graphite structure is partially expanded by incorporating molecules such as HNO3, KOH between layers to obtain a graphite-like structure with high accessibility.
[0042] The term "carbon black" as used herein refers to a form of carbon having a short-range ordered structure with a high surface area-to-volume ratio but lower than that of activated carbon. Carbon black is a material produced by the incomplete combustion of coal and coal tar, plant matter or petroleum products (including fuel oil, fluid catalytic cracking tar and ethylene cracking products).
[0043] The term "acetylene black" as used herein refers to carbon black produced by the thermal decomposition of acetylene, which has high purity, low impurity content compared to many carbon blacks, high crystallinity and well-developed structure.
[0044] The term "pyrolytic carbon" refers to any form of carbon obtained by pyrolysis of organic feedstocks or decomposition of gaseous hydrocarbons at high temperatures on a host substrate (ceramic or carbon material).
[0045] As used herein, the term "activated carbon" refers to a form of carbon having small, low volume pores that increase the surface area available for adsorption or chemical reactions. Activated carbon can be produced from a variety of raw materials, such as bamboo, coconut shells, willow peat, wood, coconut fiber, lignite, coal, and petroleum pitch, which are pyrolyzed and then subjected to a subsequent activation treatment intended to produce micropores. Carbon activation can be performed by any method known to those skilled in the art.
[0046] The carbon material used in the present invention can have different morphologies. The morphology or form of the carbon material is not particularly limited, and for example, may include particles, felts, fibers (e.g., nanofibers), silk, 2D or 3D fabrics, foams (e.g., open-cell foams), 3D printed structures, balls, cloths, blocks, extrudates (e.g., honeycombs), rods, bars and particles, tubes (e.g., nanotubes), rings, trilobes, sheets and nanosheets, and any combination thereof.
[0047] For example, the carbon material can be commercial graphite felt. The term "graphite felt" (GF) used herein refers to a textile material mainly comprising randomly oriented and interwoven carbon filaments or fibers that have been subjected to a graphitization process, and the graphitization process may involve heat treating the carbon felt at a high temperature (e.g., about 2600°C to about 3300°C). During the graphitization process, the randomly oriented and interwoven carbon filaments or fibers can be converted into an ordered graphite structure. Structuring of synthetic graphite felt is achieved by a known process called needle punching. A preferred example of a carbon material used in the present invention is graphite felt, preferably having the following dimensions: a fiber diameter of about 10 μm and a length of up to several millimeters. The fibers present a high degree of entanglement to the synthesis process and provide a high contact surface for the reactants.
[0048] Another example of a carbon material is carbon felt. The term "carbon felt" (CF) as used herein refers to a textile material that primarily comprises randomly oriented and interwoven carbon filaments or fibers. Without limitation, carbon felt suitable for use in the present invention is commercially available from, for example, Avcarb or CeraMaterials. Advantageously, the carbon felt may have a thickness of about 2 mm to about 20 mm. For example, the carbon felt may have a thickness of about 4 to about 15 mm, about 6 to about 10 mm, or about 2 to about 6 mm. For example, the carbon felt may have a fiber diameter of 0.19 mm for a fiber of 10 μm. 2 / g geometric surface area, density about 2.1g / cm 3 , BET is 4m 2 / g, or 1.9 m when the carbon contains 90% porosity 2 / g.
[0049] CF can also be used in different structures, such as flat or "rolled" structures, to provide different surface contacts and lengths depending on the downstream application. "Rolled CF" herein refers to carbon felt wound around an axis. Rolled CF can have any size; for example, its diameter can be between 20 and 2000 mm, preferably 40 to 1000 mm, most preferably 100 to 800 mm, and its length can be between 30 and 3000 mm, preferably 100 to 2000 mm, most preferably 300 to 800 mm.
[0050] Another example of a carbon material is a "carbon nanotube" or "CNT", which may refer to a hollow cylindrical or tubular carbon structure, in which a space is defined, which may be empty or filled with another material. CNTs may be closed at one or both ends. CNTs may be conceptualized as rolled graphene sheets, with a hexagonal lattice of carbon molecules, with the basal plane exposed. Depending on the degree of curling and the manner in which the original graphene sheet is formed, carbon nanotubes of different diameters and internal geometries may be formed. Carbon nanotubes formed by curling a single sheet of the above-mentioned cylinder are called "single-walled" carbon nanotubes. Carbon nanotubes whose structure is similar to a series of concentric cylinders whose diameter increases from the center to the periphery by curling multiple sheets of graphene are called "multi-walled" carbon nanotubes. Suitable carbon nanotubes for use in the present invention include single-walled carbon nanotubes and multi-walled carbon nanotubes. In certain embodiments in which the carbon nanotubes are multi-walled carbon nanotubes, the multi-walled carbon nanotubes contain 2 or more, for example 2 to 20 or 5 to 50 graphite layers. In certain embodiments, the carbon nanotubes used herein have a high aspect ratio, i.e., a length-to-diameter ratio, preferably an aspect ratio of 10 to 10,000,000: 1, such as 100 to 10,000: 1. In certain embodiments, the average outer diameter of the carbon nanotubes used herein is about 2 to 100 nm, such as about 5 to 50 nm, such as about 8 to 30 nm, such as about 20 nm. The average inner diameter of the carbon nanotubes used herein may be about 0.5 to 100 nm or about 1 nm to 50 nm.
[0051] Another example of a carbon material is a "carbon nanofiber" or "CNF," which includes a carbonaceous material comprising a solid cylindrical shape with exposed prismatic planes, mostly without spaces, meaning no hollow center, although some small channels may be present. Carbon nanofibers may be similar to carbon nanotubes (CNTs), but may include a solid core instead of a hollow center, and more reactive prismatic planes instead of basal planes exposed. Carbon nanofibers may be formed by any method known in the art, including deposition from carbonaceous vapors, such as by catalytic chemical vapor deposition (CCVD) using different gaseous carbon sources, wherein carbon is deposited on a macroscopic substrate in the presence of a transition metal catalyst, or other methods of forming carbon nanofibers known in the art.
[0052] Advantageously, the length of the carbon nanofibers can be about 100-1000nm, such as about 150-500nm. In certain embodiments, the aspect ratio of the carbon nanofibers used herein, i.e., the ratio of length to outer diameter, is preferably greater than about 10, such as greater than about 50, or greater than about 100, or greater than about 1000 or greater than about 2000.
[0053] Advantageously, the average diameter of the carbon nanofibers used herein may be less than 1000 nm. In certain embodiments, the average diameter of the carbon nanofibers is less than 500 nm, such as less than 300 nm.
[0054] It is noteworthy that both CNTs and CNFs can be grown on macroscopic substrates such as ceramics or oxides (i.e., silicon carbide, silicon dioxide, aluminum oxide, and combinations thereof), as well as on other host substrates such as activated carbon or even graphite and carbon felt. Such structured composites can allow control of flow patterns within the solid bed and increase surface contact between reactants and solids.
[0055] Other examples of suitable carbon material forms include granules having an average particle size of 0.1 to 5 mm, extrudates having an average particle size of 1 to 5 mm and a length of 2, 3, 4, 5, 6 mm or more, trilobals having an average particle size of 1 to 5 mm and a length of 1 to 10 mm, foams having a ppi (pores per inch) of 60 to 5 ppi, honeycombs having a cpsi (pores per square inch) of 5 to 900, and tubes having an aspect ratio of approximately 5:1 (i.e., 1 mm diameter × 5 mm length), 3:1 or 2:1, depending on the diameter of the material.
[0056] In some embodiments, the metal-free carbon material is not mixed with the plastic material to be converted. For example, the metal-free carbon material can be arranged as a packed bed (sometimes also referred to as a fixed bed), preferably with a 3D connected structured material to promote good continuity of the material in the entire reaction zone. Therefore, forms such as felt, fiber (e.g., nanofiber), silk, 2D or 3D fabric, foam (e.g., open-cell foam), 3D printed structure, ball, cloth, block, extrudate (e.g., honeycomb), rod-shaped, rod and particle, tube (e.g., nanotube), ring, trilobal, sheet and nanosheet are preferred. More preferably, the form is a felt, most preferably with a connected structure and a roll-shaped felt with variable length according to reaction conditions. This connected structured material allows heat to be quickly vectorized in the entire matrix of the packed bed, thereby reducing the total power input of the inductor at a given reaction temperature.
[0057] As described above, the carbon material may be a combination of at least two of the above materials.
[0058] In some embodiments, the metal-free carbon material is supported by a structure (also referred to as a substrate or a support structure) when used to prepare a reaction product. This structure can be, for example, a non-carbon structure made of aluminum oxide, silicon dioxide, silicon carbide or other oxides or ceramics or a combination thereof. The function of this support structure is to physically hold the metal-free carbon material. The support structure is not made of an inductively active material, so it does not participate in the conversion reaction. Therefore, when present, the support structure has no heating or catalytic effect. For example, a graphene coating can form a continuous film on this support structure, giving the carbon material high electrical connectivity and allowing efficient heating in an inductive mode. In contrast, the support structure itself cannot be heated by inductive heating. The coating on the surface of the support structure also allows the heat provided by the inductive heating to be generated only on the surface of the material where the reaction occurs. In order to improve electrical connectivity, a graphene coating can also be applied to the activated carbon structure. This connectivity significantly improves the heat collection from the induction coil, resulting in an increase in the temperature of the composite material. Optionally, this better connectivity can reduce the heating power to be delivered to the carbon material.
[0059] "Plastic" is to be understood in the present context in its broadest sense. In particular, plastic refers herein to any synthetic material made from organic polymers that can be injection molded while soft and then cured into a rigid or slightly elastic form. For example, the plastic can be selected from high-density polyethylene (HDPE) and low-density polyethylene (LDPE), polypropylene, polystyrene, mixed industrial waste plastics (such as low-density polyethylene, PET, PVC and polystyrene containing solid residues), plastics containing solid residues, intermediate products in plastic recycling processes (such as C 15 -C 45 or C 20 -C 40The invention relates to a method for recycling plastics, wherein the method comprises: preparing a plastic recycling process, and the method comprises ...
[0060] "C2-C4 olefin" herein refers to at least one aliphatic olefin selected from ethylene, propylene and butene. Preferably, it can be ethylene and / or propylene. According to the present invention, plastics can be converted into a specific olefin, or into a mixture of olefins. In some cases, the conversion may not be complete, and trace amounts of dienes, such as dienes prepared from ethylene, propylene and butene, may be produced.
[0061] "Other hydrocarbons" herein refers to any hydrocarbon other than C2-C4 olefins. For example, it can be a hydrocarbon having at least 5 carbon atoms, such as C5-C 10 Liquid hydrocarbons (also referred to herein as C 5+ ), or fuel oil, and / or gaseous C1 to C4 paraffin. It may refer to a mixture of at least two of these hydrocarbons.
[0062] "Direct induction heating" as used herein refers to a process in which a carbon material is directly heated by an electric current generated on the surface of the carbon material through interaction with an electromagnetic field provided by an inductor. In an embodiment of the present invention, a carbon material can be heated by generating an alternating electromagnetic field within a reaction zone containing the carbon material, wherein the alternating electromagnetic field passes through the reaction zone, thereby generating an electric current in the carbon material and heating the carbon material. Advantageously, the high inherent thermal conductivity of the carbon material allows for rapid heat transfer from the outer surface of the material to the core. Despite the high heat absorption of the reaction, the high inherent electrical and thermal conductivity of the carbon or carbon-coated material can also maintain the reaction temperature at a set temperature, and advantageously avoid the production of long-chain liquid hydrocarbons due to a decrease in the temperature within the bed.
[0063] Advantageously, the direct induction heating step may be carried out at a reaction pressure between 0.5 and 20.0 bar, such as 1 and 5.0 bar.
[0064] The present invention relates to a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising a reaction step at a temperature lower than or equal to 800° C. by means of a metal-free carbon material under direct induction heating.
[0065] The present invention also generally relates to a process for preparing C2-C4 olefins and / or other hydrocarbons, comprising a reaction step at a temperature less than or equal to 800°C by means of a metal-free carbon material under direct induction heating.
[0066] The reaction step may also be generally referred to herein as the "cleavage step," "inductive cleavage step," or "cleavage stage."
[0067] The method of the present invention can also be carried out in a two-step process. In fact, the method can include a first step (also referred to herein as the "first stage") consisting of pre-cracking the plastic before the cracking step involving IH. The first step can be carried out in the absence of a metal-free carbon material. Alternatively, in the first step, it can be carried out in the presence of certain materials that can collect heat from the furnace to improve heat transfer to the plastic, and in the second step, steam and / or liquid are blown onto the metal-free carbon material, where the cracking step occurs under direct induction heating. The liquid produced in the first stage can be in gaseous form at the outlet temperature of this stage. This temperature may vary widely between 200 and 600°C, allowing heavy hydrocarbons to remain in gaseous form when flowing downward or upward to the induction cracking stage.
[0068] The pre-cleavage step advantageously allows the production of shorter chain polymer fragments, such as C 15 -C 45 , or even C 20 -C 40 It can also vaporize plastics (e.g. waste plastics) to produce a mixture of liquid and gas. It is worth noting that the gas component can be increased by increasing the residence time of the polymer in the first pre-cracking stage. The gas component can also be increased by increasing the temperature at the outlet of the pre-cracking stage, because at high temperatures, liquid long-chain hydrocarbons will be converted into the gas component of the outlet mixture, thereby containing about 90% by weight of liquid and 10% by weight of gas, preferably 50% by weight of liquid and 50% by weight of gas, and most preferably 20% by weight of liquid and 80% by weight of gas.
[0069] The first optional step can be carried out by any method commonly used by those skilled in the art to pre-craze the plastic, such as Joule heating, induction heating and / or microwave heating. The pre-cracking step can be carried out in the presence of silicon carbide (SiC), metal beads or any thermally conductive material.
[0070] Pre-cracking conditions can be determined by those skilled in the art according to the nature and quantity of plastics, the presence of heat-conducting materials or the type of heating mode. The temperature of the first step can be between 300°C and 600°C, 350°C and 550°C, 400°C and 540°C, 450°C and 500°C, advantageously about 500°C, preferably about 450°C. For example, if Joule heating is performed, the temperature can be between 450°C and 600°C. Alternatively, if induction heating is performed, the temperature can be between 450°C and 500°C. The time of the first step can be between 5 and 100 minutes, preferably between 15 and 60 minutes, for example about 30 minutes. For example, the pre-cracking step can be implemented in a primary reactor. Then, the plastic vapor / liquid can be blown to the solid material in the secondary reactor, for example, with an inert gas (such as argon, helium or nitrogen), where a cracking process occurs. Then C2-C4 olefins and / or other hydrocarbons are obtained in the cracking step. In another mode of operation, other gases, such as hydrogen or other light hydrocarbons, can also be used as purge gases.
[0071] The first precracking step may be advantageous because it shifts the reaction towards olefins rather than other hydrocarbons, thus making the content of C2-C4 olefins higher than other hydrocarbons, compared to a process without the first step.
[0072] In one embodiment, the first step can be accomplished by directly cleaving shorter chain polymers (e.g., C 15 -C 45 , or even C 20 -C 40 ) and / or polymers previously distilled at temperatures between 200 and 500° C. These polymers can be intermediate products of plastic recycling processes.
[0073] In one aspect, the present invention also relates to a method for preparing C2-C4 olefins and / or other hydrocarbons, comprising a reaction step at a temperature of less than or equal to 800° C. by a metal-free carbon material under direct induction heating. In the method, the input material may be a plastic material as described above. For example, the plastic material may be C 15 -C 45 Olefins or C 20 -C 40 A mixture of olefins is sometimes referred to as wax. Therefore, the present invention also relates to the 15 -C 45 Olefins or C 20 -C 40 A process for converting olefins into C2-C4 olefins and / or other hydrocarbons, preferably into C2-C4 olefins.
[0074] The method can be operated in a continuous mode, so the operating time of the different steps depends on the amount of plastic to be processed. For example, the time of the "cracking step" can be between 2 and 20 minutes, such as about 10 minutes.
[0075] Depending on the carbon nature of the cracking step, i.e., non-porous vs. porous, the liquid component and gaseous component can be adjusted by changing the reaction conditions. For example, under certain reaction conditions, on non-porous materials, as shown in the example, the gaseous component can be produced as the main component, and the main product is light olefins, while on porous materials, the liquid component is higher relative to the gaseous component, depending on the reaction temperature. 25 .
[0076] Advantageously, at the end of the cracking step, the resulting liquid hydrocarbons (also referred to as "liquid component") can be condensed and / or the resulting gaseous products (also referred to as "gas component") can be directed to a gas chromatograph for analysis. Advantageously, the gas component can contain at least 5.0 mol% of unsaturated C2 to C4 hydrocarbons, preferably at least 30.0 mol% or preferably at least 50.0 mol% or preferably at least 70.0 mol% of unsaturated C2 to C4 hydrocarbons.
[0077] Advantageously, the liquid components produced on the porous carbon material can be directly used in different chemical processes, i.e., as fuel for transportation, or can also be recycled back to the carbon material for cracking into light olefins, i.e., C2-C4 olefins.
[0078] In some embodiments, the present invention relates to a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising:
[0079] - a step of pre-cracking the plastic, and
[0080] - A reaction step by means of a metal-free carbon material under direct induction heating at a temperature lower than or equal to 800°C.
[0081] In some embodiments, the present invention relates to a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising:
[0082] - a step of pre-cracking the plastic at a temperature between 300° C. and 600° C. by induction heating, Joule heating or microwave heating, and
[0083] - A reaction step by means of a metal-free carbon material under direct induction heating at a temperature lower than or equal to 800°C.
[0084] In some embodiments, the present invention relates to a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising:
[0085] - a step of pre-cracking the plastic on metal beads or any heat-conducting material mixed with the plastic, and
[0086] - A reaction step by means of a metal-free carbon material under direct induction heating at a temperature lower than or equal to 800°C.
[0087] In some embodiments, the present invention relates to a method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising:
[0088] - a step of pre-cracking the plastic, and
[0089] - a reaction step by means of a metal-free carbon material under direct induction heating at a temperature lower than or equal to 800° C.,
[0090] In the pre-cracking step, the plastic is pre-cracking in the primary reactor, and the vapor and / or liquid produced in the first stage (later in a gaseous state at a temperature of 200 to 400° C.) is blown by a gas stream to the material in the secondary reactor, where cracking occurs.
[0091] The invention is further described by the following examples with reference to the accompanying drawings, which should not be construed as limiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0092] Figure 1 : Shown is the plastic to olefin (PTO) process (selectivity, wt%) on a planar carbon felt (CF) material for converting injection molded HDPE as a function of reaction temperature under direct induction heating. (AB) Distribution of gaseous and liquid products (H2 and C n ), (CD) gaseous product distribution (H2 and C1-C7). Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), CF weight = 0.54 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450°C, CF temperature = variable.
[0093] Figure 2 : Shown is the plastic to olefin (PTO) process (selectivity, wt %) on a planar carbon felt (CF) material for converting injection molded HDPE as a function of reaction temperature under indirect Joule heating. (A, B) Distribution of gaseous and liquid products (H2 and C n , including almost solid wax), (C, D) gaseous product distribution (H2 and C1-C7). Reaction conditions: HDPE weight = 6g (mixed with 2g SiC to improve heat transfer), CF weight = 0.54g, reactor diameter = 26mm, argon flow rate = 15mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1), CF temperature = variable.
[0094] Figure 3: shows the plastic-to-olefin (PTO) process (selectivity, weight %) on roll CF material as a function of reaction temperature under direct induction heating for converting injection molded HDPE (A, C, E), and (B, D, F) C2-C4 olefins versus C1 to C7 gaseous products saturated composition comparison. Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), roll CF weight = 1.2 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ), CF temperature = variable.
[0095] Figure 4 : Shown is the plastic-to-olefin (PTO) process (selectivity, wt%) on CF materials (i.e., planar and roll CF), operating in IH mode at 550°C for planar CF and 500°C for roll CF, for converting injection molded HDPE plastic to light olefins. (A, C) Product distribution. (B, D) Olefins versus gaseous saturated C2-C4 components. Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), CF weight = 0.54 g (planar CF) and 1.2 g (roll CF), reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0096] Figure 5 : Shown is a plastic to olefin (PTO) process (selectivity, wt %) using mixed industrial polymer waste on CF materials (i.e., planar and roll CF), operating at 550°C for planar CF and 500°C for roll CF in IH mode, for converting industrial mixed waste plastics into light olefins. (A, C) Product distribution and C2-C4 components on roll CF material, (B, D) Product distribution and C2-C4 components on planar CF material. Reaction conditions: mixed industrial plastic weight = 6 g (mixed with 2 g SiC to improve heat transfer), CF weight = 0.54 g (planar CF) and 1.2 g (roll CF), reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0097] Figure 6 shows a cyclic test of a plastic-to-olefin (PTO) process on a roll CF material (26 mm diameter, 15 mm height) at 450°C, operating in IH mode for converting industrial mixed waste plastics into light olefins. (AC) Product distribution as a function of the cyclic test. (DF) Comparison of olefins and saturated C2-C4 components as a function of the cyclic test (cycle 1, cycle 3, and cycle 9). Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), CF weight = 1.2 g (roll CF), reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 or 30mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0098] Figure 7 The (A) gas and liquid component distribution and (B) olefin C2-C4 composition as a function of the cycle test during the PTO process on a roll CF material (26 mm diameter, 15 mm height) at 450°C, operated in IH mode for converting industrial mixed waste plastics into light olefins. Reaction conditions: Mixed waste plastic weight = 6 g (mixed with 2 g SiC to improve heat transfer), CF weight = 1.2 g (roll CF), reactor diameter = 26 mm, argon flow rate = 30 mL.min per cycle -1 , vaporization temperature = 450℃.
[0099] Figure 8 shows the plastic-to-fuel (PTF) process (selectivity, wt%) using injection molded HDPE polymer on 3 mm MESOC+ material pellets under direct induction heating (500 °C) and indirect Joule heating modes (500 and 550 °C). (A, B) Liquid and gaseous product distributions (H2 and C n ) and gaseous product distribution (H2 and C1-C7). (CF) Liquid and gaseous product distribution (H2 and C1-C7) under indirect Joule heating n , including solid wax) and gaseous product distribution (H2 and C1-C7). Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), MESOC+ weight = 3 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0100] Fig. 9The plastic-to-fuel (PTF) process (selectivity, wt %) on (A, B) 3 mm MESOC+ particles and (C, D) 1 mm MESOC+ particles under induction heating at 500°C is shown. Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), MESOC+ weight = 3 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0101] Fig.10 The plastic-to-fuel (PTF) process (selectivity, wt %) using injection molded HDPE polymers (A, B) and blended industrial polymers (C, D) on 3 mm particles of MESOC+ material under direct induction heating is shown. Reaction conditions: HDPE weight = 6 g (blended with 2 g SiC to improve heat transfer), MESOC+ weight = 3 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ), MESOC+temperature=500℃.
[0102] Figure 11 shows the cyclic tests (selectivity, wt%) of the plastic-to-fuel (PTF) process on 3 mm particles of MESOC+ material operating in IH mode at 500°C for converting injection molded HDPE into fuel. (A, C, E) Product distribution as a function of cycle number (AB: cycle 1, CD: cycle 2, EF: cycle 3). (B, D, F) Comparison of olefin and saturated C2-C4 components as a function of cycle number. Reaction conditions: HDPE weight = 6 g (mixed with 2 g SiC to improve heat transfer), MESOC+ weight = 3 g, reactor diameter = 26 mm, argon flow rate = 15 mL.min -1 , HDPE vaporization temperature = 450℃ (heating rate 20℃.min -1 ).
[0103] Figure 12 shows the plastic-to-olefin (PTO) process of HDPE under different conditions. A) Two-step PTO process results on carbon felt (CF) roll catalyst. B) One-step PTO process results on carbon felt (CF) roll catalyst. C) One-step PTO process results on metal catalyst. n (C5 to C 40 ) (Figures A and B) or the yields of H2, C5 and wax produced (Figure C). The following figures show the yields of H2 and C1 to C7 (weight %) (Figures A, B and C). DETAILED DESCRIPTION
[0104] Example
[0105] Example 1: Materials for implementing the method of the present invention
[0106] The device for implementing the present invention comprises a first part, which is a polymer supply, which may contain a polymer weight of about 5 to 100 g. The reservoir of the polymer supply part is filled with an argon flow (30 mL.min -1 ) was continuously purged to avoid any air penetration into the reservoir. The polymer extrudate was fed into a vaporization stage (Joule heating) in an electric furnace maintained at 450°C and heated at 15 to 60 mL.min -1 The reaction mixture is continuously purged with an argon flow of varying flow rates. The polymer vapor produced in this stage is brought to the reaction part (also called "cracking stage") operated under direct non-contact induction heating (IH) or indirect Joule heating (JH) at different temperatures. The reaction products are further passed through a trap maintained at 16°C for condensing liquid hydrocarbons, while the gaseous products are directed to a gas chromatograph (GC) for analysis. The reaction products are analyzed online by two VARIAN 3800 gas chromatographs. The first gas chromatograph is equipped with two detectors (a thermal conductivity detector (TCD) connected to an Agilent J&W DB-1 column and a flame ionization detector (FID) connected to an Agilent J&W CarboBOND column), which are used to analyze H2 / CH4 and up to C 12 The second gas chromatograph was equipped with a FID detector connected to a Restek RT alumina BOND column to separate lighter hydrocarbons such as C2H2, C2H4, and C2H6 and other hydrocarbons up to C7. A calibration curve was used to separate CH4, H2, C2 components, C6H6, C7H8, C8H 10 and C 10 The other hydrocarbons were quantified using the Dietz factor method using the FID integrated area.
[0107] IH experiment The experiments were carried out on an 8310 induction heating device (10 kW, Ambrell Ltd) equipped with a spiral 6-turn induction coil (L = 1.05 m, pure coil resistance = 2.066 × 10 -3 Ω) and an external cooler with a circulating water / glycerol (10%) mixture as cooling medium. In a typical experiment, a quartz reactor containing material (similar to that used by JH) was placed inside the induction heater coil. Real-time temperature control / regulation was ensured by a PID system (proportional-integral-derivative controller, Eurotherm model 3504) coupled to a laser pyrometer ( Power <1mW, located at a distance of ≈30cm from the material), the laser pyrometer is focused in the middle of the material bed and is capable of operating in the range of 150-1000°C. In the temperature range of 160-300°C, the system allows a heating / cooling rate of approximately 300°C min -1 It is worth noting that the inductor operates at a frequency of 263kHz, which produces a much lower magnetic field than those operating at lower frequencies (i.e. <10kHz). In fact, the magnetic field from low-frequency induction is more penetrating to surrounding materials. However, to further reduce worker exposure to the magnetic field, the device is placed in a Faraday cage surrounded by a metal mesh.
[0108] For indirect Joule heating, the material is placed in an electric furnace set at the reaction temperature and controlled by thermocouples inserted into the ceramic portion of the furnace.
[0109] For both PTO and PTF processes, injection molded plastics, namely high-density polyethylene (HDPE), and mixed industrial plastics, namely low- and high-density polyethylene (LDPE) and polystyrene (PS) with solid residues, were investigated.
[0110] Two types of carbon materials were used in this work: (i) low specific surface area (4 m 2 / g) nonporous carbon felt (commercialized by MERSEN), consisting of entangled carbon filaments with an average diameter of about 10 μm and a length of several hundred micrometers, and (ii) industrially produced porous carbon (MESOC+, commercialized by SICAT SARL) with a specific surface area of 300 m 2 / g, and is composed of a large mesoporous network. The different properties of these carbon-based materials are shown in Tables 1 to 3.
[0111] Table 1: Characteristics of different carbon materials used in the process.
[0112]
[0113] Table 2 summarizes the detailed properties of the carbon felt according to the buyer.
[0114] Table 2: Properties of pristine carbon felt (information provided by supplier).
[0115] performance Numeric Density at 20℃ 0.08g / mL Carbon content 99.5% Ash 500ppm Specific Heat 0.71J / g / ℃ Average specific heat 1.67J / g / ℃ Emissivity 0.99 Sublimation temperature 3600 Surface area (nitrogen) <![CDATA[4±3m 2 / g]]> Thermal conductivity - Approximate processing temperature 2500℃
[0116] Table 3 summarizes the detailed characteristics of MESOC+ according to the buyer.
[0117] Table 3: Typical properties of the new MESOC+ (information for 3 mm particles provided by the supplier).
[0118]
[0119]
[0120] Example 2: Polymer cracking process
[0121] PTO on non-porous carbon felt material
[0122] Carbon felt (CF) purchased from Mersen was used without any pretreatment. CF consists of tangled microfilaments with an average diameter of about 10 μm and a length of several hundred microns. The CF microfilaments are very smooth, with almost no internal pores and roughness, which is consistent with their low specific surface area. The material also shows a high open porosity of up to about 90% by volume.
[0123] In order to be used as a metal-free material, CF can be directly cut into flat disks, called flat CF, or cut into sheets, which can be further rolled up to produce a cylindrical shape, called rolled CF. Rolled CF material appears to be a very good structure for use as a carbon material for plastic conversion processes, because its length can be easily adjusted, which allows adjustment of the bed height to control the contact time and exposed surface with respect to plastic vapor / liquid, thereby increasing the yield of light olefins. In fact, in the case of the rolled CF structure, this control of the bed height is very effective, because the arrangement of the rolled CF pieces in the reactor results in uniform heating of the solid bed. In fact, the close contact between the rolled CF pieces does not cause local overheating, which leads to uneven temperature distribution within the solid bed and excessive decomposition of intermediate compounds into carbon.
[0124] PTO process on injection molded HDPE plastic waste
[0125] In this example, injection molding of waste plastics (HDPE) into light olefins was performed on CF materials under direct induction heating (invention) and indirect radiant Joule heating (comparative example). The results obtained, as a function of reaction temperature, are as follows: Figures 1 to 4 shown.
[0126] The cracking performance on the planar CF material operated in IH mode increases from 500°C to 550°C, i.e., the gas composition increases from 53% to 76% ( Figure 1 AB). Figure 1 As shown in AB, the liquid component is mainly composed of C 19 To C 30 of long-chain hydrocarbons, with a small amount of C 30 To C 35 The small amount of long-chain hydrocarbons can be attributed to the high porosity of the CF material, i.e., 90% of the empty volume, which may have favored some bypassing of the polymer vapor during the test. Blank tests performed under Joule heating with quartz wool instead of CF yielded only long-chain hydrocarbons (C>30) that were not soluble in any solvent, and no hydrocarbons with a carbon chain less than 30 were observed.
[0127] The C2-C4 olefins and saturated gas components obtained on the planar CF material under IH with the change of reaction temperature also showed the same trend. The yield of C2-C4 olefins was 33% at 500℃ and 51% at 550℃. Figure 1 CD).
[0128] It is noteworthy that the color of the produced liquid hydrocarbons also changes with the reaction temperature, i.e., becomes darker with increasing reaction temperature. This color change can be attributed to the presence of polyolefins or aromatics in the product. It is expected that high reaction temperatures favor such products.
[0129] The PTO process was also carried out on CF materials operated under indirect Joule heating (comparative example) with varying reaction temperatures. Figure 2 AD. At 500 °C, only wax was obtained on the CF material, and the results are not reported because this wax is difficult to dissolve in the solvent for GC analysis. The product distribution in JH mode is completely different because the gas component is only 23 and 39 wt% at reaction temperatures of 550 °C and 600 °C, respectively ( Figure 2 A and B). Among the gaseous components, C2-C4 olefins are dominant. At 550°C and 600°C, their absolute weight % is 12% and 22% by weight of the initial weight of the waste plastic, respectively. The liquid component recovered at the reactor outlet is mainly composed of insoluble wax, such as Figure 2 Digital photographs are shown in the insets of A and B.
[0130] These results clearly demonstrate the high efficiency of direct IH mode operation of carbon materials for PTO processes at low reaction temperatures. The high PTO efficiency observed on CF materials under IH can be attributed to several facts: (i) high temperature maintenance efficiency due to the high heating rate of IH, i.e., temperature regulation of several hundred degrees per minute to maintain the material temperature for the endothermic cracking reaction; and (ii) better temperature uniformity throughout the solid bed, because the heat is directly generated in the body of the material, rather than indirectly transferred by convection / conduction as in the indirect Joule heating mode. In fact, carbon felt is a well-known insulator shielding material to prevent heat transfer from high-temperature furnaces, and therefore, due to the large void content in the material, the carbon filaments show high heat transfer along their filamentary structure rather than between filaments. In the case of IH, the entire solid volume can be heated, while in the case of JH, the heat is transferred along the outer filaments to the core of the solid bed, which is more susceptible to the filamentary structure of the material. This thermal resistance can be avoided by IH because the heat is directly generated through the body of the material as described above, and the heat distribution throughout the carbon filaments is much faster due to the small diameter of the filaments, which is kept within the depth penetration range of the eddy current, i.e., a few microns from the outer surface. The high aspect ratio (ratio of length to diameter) of the carbon microfilaments that make up CF materials also facilitates rapid heat conduction along the filaments and through the entire material matrix, greatly improving the reaction process. Figure 1 and Figure 2 The results clearly demonstrate the advantages of operating the PTO process via direct non-contact induction heating mode.
[0131] Effect of CF macroscopic shape
[0132] In this data set, roll CF material is used instead of planar CF material, and the results varying with reaction temperature are shown in FIG3 . At a reaction temperature of 500° C., the main part of the starting plastic is converted into light hydrocarbons (FIG. 3C and 3D), while this is not the case for a lower reaction temperature, i.e., 450° C. (FIG. 3A and 3B), where some liquid components are observed. At 500° C., C2-C4 olefin components account for 46% of the total hydrocarbon products (FIG. 3D), which are mainly composed of ethylene and propylene, while methane accounts for about 13% by weight. Increasing the reaction temperature from 500° C. to 550° C. results in a sharp increase in cracking products, with a significant increase in methane contribution, i.e., 29% by weight (FIG. 3F), while light olefins are significantly reduced. Ethylene is still the main light olefin, about 22% by weight (FIG. 3F). The results obtained show that at the same reaction temperature, roll CF shows higher cracking performance than planar CF (same apparent volume). Such results can be attributed to the orientation of CF within the induction coil, i.e., circular curl, which can facilitate the eddy current circulation of the induction heater within the CF sheet, thereby leading to higher heat collection and temperature homogenization within the solid bed.
[0133] Figure 4 The PTO results obtained on the planar and roll CF materials were compared. According to the results, the roll CF showed higher PTO performance compared to the planar CF because the roll CF material achieved the same C2-C4 olefin cracking and production at a lower reaction temperature than the planar CF material (i.e., 500°C vs. 550°C). Figure 4 B and D). High carbon hydrocarbons (i.e. >C 25 ) is also significantly lower, which confirms that the scroll CF material can efficiently cleave the long-chain polymer ( Figure 4 A and C). Such results can be attributed to the difference in carbon filament density between the two structures. In fact, in the case of CF produced by the needle punching process, higher bypass channels in the planar structured material should be expected compared to the laterally exposed roll material. The circular orientation of the roll CF material also favors the induction current, which improves the axial heat transfer.
[0134] PTO process on industrial plastic waste
[0135] In this example, the PTO process was studied on CF materials (i.e., flat and rolled) using a mixture of plastic waste from different industrial sources (Table 4). The waste plastics were heat treated at 250 °C under argon to melt the polymers and measure the exact content of inorganic solids in the samples.
[0136] Table 4: Composition of mixed industrial polymer waste and sources of waste. PE > 50 wt%, PS < 20 wt%, while the other components are non-plastic solid waste.
[0137]
[0138] The results show that, regardless of shape and structure, CF materials operated in IH mode show high cracking performance to convert mixed industrial polymers into liquid and gaseous hydrocarbons ( Figure 5 A and B). Both materials also showed high selectivity for C2-C4 olefins at reaction temperatures as low as 500°C ( Figure 5 C and D). On the 500°C rolled CF material, the C2-C4 olefin component is about 43%, while on the 550°C flat CF material it is about 49%. In both cases, ethylene and propylene are the main products of this C2-C4 olefin component. The very similar results obtained on both CF materials when operating the PTO process with industrial mixed polymers can be attributed to their lower density compared to the injection molded polymer, i.e. a mixture of LDHP and HDPE instead of pure HDPE which is easily cracked.
[0139] Table 5 summarizes the results obtained in different tests (including injection molded HDPE and mixed industrial waste plastics) and compares them with those reported in the literature.
[0140] Table 5:
[0141]
[0142] Stability over Cyclic Tests
[0143] The stability of the CF material for the conversion of mixed industrial wastes into light olefins was investigated and the results are shown in Figure 6. The cycling tests were performed on the rolled CF material at 450 °C, which according to previous results is the most suitable temperature for the PTO process on this material.
[0144] According to the results, the rolled CF material showed high and stable PTO activity over the cyclic test using mixed industrial polymers. This high stability can be attributed to the fact that the process is carried out in two steps, in which the waste polymer is first vaporized in the upper hot bed and then the polymer vapor is cracked in the second reactor containing the CF material. The polymer vapor passes through a quartz wool plug, which acts as a scavenger or filter to block impurities from the polymer waste and prevent excessive deactivation of the carbon material. By operating in these separate sections, the main impurities contained in the original waste plastic remain in the first hot bed, while very few impurities (mainly in gaseous form) pass through the reaction bed, which contributes to its stability over the cyclic test. In addition, a layer of 1mm MESOC+ extrudate (2mm long) is added on top of the rolled CF material, slightly away from the induction coil, at a temperature of about 450°C, thereby acting as a scavenger layer and better evaporating the adsorbed polymer vapor. It is worth mentioning that at this temperature, i.e., 450°C, the MESOC+ sample shows very low activity and has no ability to produce light olefins. The gas, liquid and solid residue components obtained after each cycle at 450°C are Figure 7 It is shown in Figure 3 and confirms the high stability of the rolled CF material for the PTO process.
[0145] The weight of the solid residue deposited as a function of the cycle test was also measured. According to the results, for the first five cycle tests at 500°C, the weight of the carbon material slightly increased by about 0.6±0.3 wt% after each cycle.
[0146] PTF on porous carbon materials
[0147] Porous carbon, called MESOC+, is industrially produced by Sicat SARL (www.sicatcatalyst.com) in the form of extrudates of different macroscopic shapes. For the PTF process, MESOC+ extrudates with a diameter of 1 or 3 mm and a length of 2 to 4 mm were used. Low-resolution SEM micrographs taken on MESOC+ demonstrate the roughness of its surface taken at different angles. Medium-resolution SEM micrographs demonstrate the presence of macropores and a highly mesoporous structure in the material, which can facilitate the adsorption and cracking of pyrolytic polymer vapors.
[0148] PTF process on injection molded HDPE plastic waste
[0149] In this section, injection molding waste plastics (HDPE) were converted into HC on MESOC+ materials under direct induction heating (the present invention) and indirect radiant Joule heating (comparative example). The results are shown in Figure 8. At the same reaction temperature of 500°C, 3mm MESOC+ exhibited lower cracking activity than CF materials, i.e., flat or rolled CF materials. However, it is worth noting that even at higher temperatures, the performance obtained on 3mm MESOC under IH is still much higher than that in JH mode (Figure 8A vs. 8C and E). Such results can again be explained by the higher heat retention in the carbon bed. Polymer long chain cracking is an endothermic process, so the efficiency of the solid material is strongly affected by the effective temperature distribution in the bed and on the carbon surface where the reaction occurs. At high cracking rates, the material temperature may decrease, thereby reducing the cracking performance, which is the root cause of the formation of long-chain hydrocarbons or waxes. Unlike induction heating, the low heat supply using the indirect heating mode cannot maintain the optimal bed temperature because the heat is generated directly in the material body.
[0150] However, it is worth noting that the 3 mm MESOC+ material produces mainly saturated components, but also C6 to C 20 Liquid hydrocarbons ( Fig. 9 These results differ from those obtained on nonporous CF materials operated under similar reaction conditions, where light olefins (C 2= -C 4= ) dominated. These results can be explained by the following facts: (i) unlike non-porous CF, the porous nature of MESOC+ can favor the diffusion of original light olefins within the pores of the material, thereby facilitating the formation of long-chain olefins or aromatics through the recombination of light olefins, and (ii) compared with CF, 3 mm MESOC+ also showed a higher diffusion length, i.e. 3 mm in diameter versus 10 μm, which may produce an internal temperature gradient inside the extrudate with lower cracking performance. This hypothesis was investigated by changing 3 mm MESOC (3 mm in diameter) to 1 mm MESOC+ (1 mm in diameter). The comparison results are shown in Figure 5. Fig. 9 According to the results, although some C6 to C 15 range, but the smaller carbon material, i.e. 1 mm MESOC+, showed improved selectivity to light olefins. On 3 mm MESOC+, long chain hydrocarbons up to >C 23 , while on 1mm MESOC+, only C 15of hydrocarbons. This result can be explained by the fact that for the 3 mm MESOC+ material, heat is transferred from the outer surface to the inner part of the particle, since the inductive heating of the conductive material mostly starts from the outer surface (skin effect) and then the temperature is transferred to the material inward by conduction. Therefore, the solid temperature of the 1 mm particles is expected to be more uniform than that of the 3 mm particles, resulting in an increased cracking activity of the polymer vapor. The small diameter of the 1 mm MESOC also improves the geometrical contact surface between the polymer vapor and the outer surface of the hot material, thereby improving the cracking performance. However, it is worth noting that the MESOC+ material still exhibits a lower C2-C4 olefin yield compared to the CF material. This result can be explained by the presence of pores in the MESOC+ material, which may favor side reactions, namely aromatization, while the lack of pores in the CF material prevents this side reaction. However, it is worth mentioning that liquid hydrocarbons produced by the pyrolysis of waste plastics may also be a beneficial option, as these products can be converted into different fuel components with low sulfur content, namely gasoline, diesel and jet fuel.
[0151] PTF process on industrial plastic waste
[0152] Plastic pyrolysis was also investigated on MESOC+ materials using mixed plastic waste from different industrial sources (Table 4). Fig.10 ) showed that the 3 mm MESOC+ material operated in IH mode showed high cracking performance and high selectivity for light olefins from industrial mixed plastic waste at relatively low reaction temperatures (Figure 11C and D). The formation of a small amount of long-chain liquid components can be attributed to the low vaporization temperature of the mixed polymer containing LDPE, which can provide more polymer vapor at the same pyrolysis temperature compared to injection molded HDPE.
[0153] Stability over Cyclic Tests
[0154] The stability of the 3mm MESOC+ material for converting injection molded HDPE to light olefins and fuels was investigated and the results are shown in Figure 11. 3mm MESOC+ showed intermediate performance for all cycles tested, with a gas component of approximately 55% and a liquid component of approximately 42%. However, it can be noted that for cycle #3, a decrease in the long chain hydrocarbons (i.e., >C 17) slightly increased, which may be attributed to the partial blockage or coating of some active sites at the origin of the cracking process (Figure 11E). According to these results, the 3mm MESOC+ material is able to convert waste plastics into liquid and gaseous hydrocarbons for downstream applications such as polymer processing (ethylene and propylene components) or liquid feedstocks for transportation or petrochemical processing. From cycle #1 to cycle #2, the C2-C4 component decreased from 38% to 28%, remaining unchanged in cycle #3, while the C2-C4 olefin component increased from 15% to 17% and 20% for cycle 1, cycle 2 and cycle 3. The obtained results once again confirm the ability of the MESOC+ material to convert waste plastics into hydrocarbons that can be used in many petrochemical processes.
[0155] in conclusion
[0156] In summary, an effective combined use of metal-free carbon materials and direct induction heating is reported for the conversion of injection molded or industrial mixed plastics (such as waste plastics) into C2-C4 light olefin components (especially on non-porous CF materials) as well as liquid hydrocarbons (especially on porous MESOC+ materials). The results show that carbon materials, non-porous materials (such as carbon felt) or porous materials, effectively perform this direct conversion at relatively low temperatures in induction heating mode. The carbon materials also show high stability over cyclic tests, which once again confirms their benefits for this process. In this conversion process, the carbon material is directly heated by eddy currents generated on the surface of the material through interaction with the electromagnetic field provided by the inductor. The high intrinsic thermal conductivity of carbon-based materials significantly improves the heat transfer from the outer surface of the material to the core. It is expected that the heat transfer is more efficient in the case of carbon felt because the relatively small diameter of the carbon microfilaments, i.e., 10μm, remains within the depth penetration range of the eddy currents compared to the larger diameter (≥1mm) of mesoporous carbon microfilaments. This high heat transfer in carbon felt can further explain the higher light olefins yield from plastic waste compared to that observed on larger mesoporous carbons, where the temperature gradient within the particles may hinder the cracking reaction, resulting in the formation of more liquid components under the same reaction conditions. The difference in light olefins yield between CF and MESOC+ materials may also be due to diffusion phenomena caused by the pores and geometric structures of the two materials. Induction heating also provides an elegant way to directly heat the material without the excessive energy losses through convection and conduction that are usually observed in the case of indirect Joule heating. The results also suggest that carbon materials with smaller sizes, i.e., macroscopic host substrates modified with carbon nanotubes or nanofibers, can also be effectively heated using induction heating for conducting PTO or PTF processes.
[0157] For injection molding waste plastics (HDPE) and mixed industrial waste plastics containing impurities, non-porous carbon felt (CF) shows high selectivity for C2-C4 olefin components (mainly ethylene and propylene components) in the reaction temperature range of 450 to 550°C. C2-C4 olefins can be finely adjusted by modifying operating parameters such as temperature or contact time. The material also shows high stability over the changes in cyclic tests using industrial mixed waste plastics, highlighting the advantages of using this metal-free carbon material. In addition to C2-C4 olefin components, waste plastics can also produce other liquid hydrocarbons, which can be further used in other downstream applications or recovered at the top of the reactor to produce low-carbon olefin components.
[0158] The MESOC+ porous carbon material showed a lower yield of light olefins and about 50% of the higher C5 to C 20 Liquid hydrocarbon components. Mesoporous carbon materials also showed high stability over cycling tests, confirming their benefit for this process.
[0159] It is noteworthy that at reaction temperatures ≤ 500 °C, the yields of aromatic compounds on non-porous and porous carbon materials are extremely low compared to linear or branched hydrocarbons, which may be due to the lack of strong acidity on these carbon materials, unlike those present on zeolite catalysts. These results are of great benefit because aromatic formation helps to enhance the hydrogen pool, which can react with unstable intermediate olefins to give saturated products. The obtained results show that non-porous carbon materials with no internal pores and very low specific surface area, namely carbon felt, mainly produce higher light olefins, which can be attributed to the high desorption rate of light olefin intermediates, as well as less aromatic formation, which reduces the hydrogen available for hydrogenation of such intermediates. On the other hand, porous carbon, which can induce longer residence time, leads to the formation of higher liquid components and lower light olefin components in the gaseous products.
[0160] Example 3: Comparison between plastic-to-olefin processes for HDPE using rolled carbon felt or metal sheets
[0161] The first experiment (comparative example) was carried out with a metal sheet made of an alloy of iron and nickel in the form of a metal spring with the following dimensions: length 50 mm, diameter 4 mm, which was inductively heated to 500° C. and then the polymer extrudate was directly sent to the reaction zone. Fig. 12C shown.
[0162] The second experiment (the present invention) was carried out under the same conditions using rolled carbon felt (CF) as the metal-free carbon material. Fig. 12B shown.
[0163] T1 refers to the flow temperature before the reactor inlet, and T2 refers to the conversion reaction (or cracking) temperature. For these two experiments, T1 = 25°C, T2 = 500°C.
[0164] Reaction conditions: M of CF (H = 40 mm) = 1.7 g, M of metal (H = 35 mm) = 4 g; M HDPE =20g; F AR =30mL.min -1 CF and metal flakes directly fall onto the catalyst = 5 g HDPE .h -1
[0165] The conversion result is as follows Fig. 12C shown.
[0166] In both experiments, the gas component accounted for 64%, the liquid component accounted for 33%, and the residue accounted for 3%. However, the experiment using the metal sheet converted the polymer extrudate to about 99.46 wt% wax and about 0.54 wt% C2-C4 olefins, while the experiment using the rolled CF converted the polymer extrudate to about 42 wt% C2-C4 olefins.
[0167] These results indicate that, in contrast to the metal-free carbon materials used in the process of the present invention, the induction-heated PTO process using metal catalysts is unable to obtain C2-C4 olefins.
[0168] Example 4: Comparison between plastic-to-olefin processes for HDPE using rolled carbon felt in a one-step or two-step process
[0169] Two experiments were performed using rolled CF: conversion reaction in a one-step process (i.e., directly proceeding to the pyrolysis step) or conversion reaction in a two-step process (i.e., pre-pyrolysis in the first step, followed by a pyrolysis step using a metal-free carbon material).
[0170] T1 refers to the flow temperature or the first step temperature (if any), and T2 refers to the conversion reaction (or cracking) temperature. For the one-step process, T1 = 25°C, T2 = 500°C. For the two-step process, T1 = 450°C, T2 = 500°C.
[0171] Reaction conditions: M = 1.7 g of roll CF (H = 40 mm); M HDPE =20g; T HDPE =450℃(JH);F AR =30mL.min -1 The raw materials of CF catalyst were divided into two steps: the first step: pyrolysis by Joule heating ("JH"), the second step catalysis = 10g HDPE .h -1 CF raw material directly dropped onto the catalyst = 5 g HDPE .h -1 .
[0172] Fig. 12B The results of the one-step method are shown. Fig. 12AResults of a two-step approach are shown.
[0173] For the one-step process, the gas component accounts for 64 wt%, the liquid component accounts for 33 wt%, and the residue accounts for 3 wt%. For the two-step process, the gas component accounts for 69 wt%, the liquid component accounts for 23 wt%, and the residue accounts for 8 wt%. The one-step process converts the polymer extrudate to about 42 wt% C2-C4 olefins, while the two-step process converts the polymer extrudate to about 48 wt% C2-C4 olefins.
[0174] These results indicate that the presence of the first step increases the conversion of C2-C4 olefins, which is beneficial.
[0175] References
[0176] 1.Onwudili JA, Muhammad C., Williams PTInfluence of catalyst bedtemperature and properties of zeolite catalysts on pyrolysis-catalysis of asimulated mixed plastics sample for the production of upgraded fuels and chemicals.J.Energ.Inst.92, 1337-1347(2019).
[0177] 2. Lopez G., Artetxe M., Amutio M., Bilbao J., Olazar MA review onthermal and catalytic pyrolysis of plastic solid waste (PSW). Thermochemical routes for the valorization of waste polyolefinic plastics to produce fuels and chemicals. A review. Renewable Sustainable Energy Rev. 73, 346-368 (2017).
[0178] 3.Dogu O.,Pelucchi M.,Van de Vijver R.,Van Steenberge P.H.M.,D’hoogeD.R.,Cuoci A.,Mehl M.,Frassoldati A.,Faravelli T.,Van Geem K.M.The chemistryof chemical recycling of Solid plastic waste via pyrolysis and gasification:state-of-the-art,challenges,and future directions.Prog.Energy Combust.Sci.84,100901(2021).
[0179] 4.J-P.Lange,Managing Plastic Waste-Sorting,Recycling,Disposal,andProduct Redesign,ACS Sustain.Chem.Eng.,2021,9,15722-15738https: / / doi.org / 10.1021 / acssuschemeng.1c05013.
[0180] 5.Layritz,L.S.,Dolganova,I.,Finkbeiner,M.,Luderer,G.,Penteado,A.T.,Ueckerdt,F.,et al.(2021).The Potential of Direct Steam CrackerElectrification and Carbon Capture&Utilization via Oxidative Coupling ofMethane as Decarbonization Strategies for Ethylene Production.Appl.Energ.296,117049.doi10.1016 / j.apenergy.2021.117049.
[0181] 6.Schiffer Z.J.,Manthiram K.Electrification and Decarbonization ofthe Chemical lndustry.Joule 1,10-14(2017).
[0182] 7.Jie X.,LiW.,Slocombe D.,Gao Y.,Banerjee I.,Gonzalez-Cortes S.,YaoB.,Almegren H.,Alshihri S.,Dilworth J.,Thomas J.,Xiao T.,EdwardsP.Microwave-initiated catalytic deconstruction of plasfic waste into hydrogen and high-value carbons.Nat.Catal.3,902-912(2020).
[0183] 8.Zhou N.,Dai L.,Lv Y.,Li H.,Deng W.,Guo F.,Chen P.,Lei H.,RuanR.Catalytic pyrolysis of plastic wastes in a continuous microwave assistedpyrolysis system for fuel production.Chem.Eng.J.418,129412(2021).
[0184] 9.Wang,W.,Tuci,G.,Duong-Viet,C.,Liu,Y.,Rossin.A.,Luconi,L.,Nhut,J.-M.,Nguyen-Dinh,L.,Giambastiani,G.,Pham-Huu,C.,2019.lnduction heating:anenabling technology for the heat management in catalytic processes,ACSCatal.,2019,9,7921-7935.Khattak et al.,2019
[0185] 10.Haneishi N.,TSubaki S.,Abe E.,Maitani M.M.,Suzuki E.,Fujii S.,FukuShima J.,Takizawa H.,Wada Y.,2019.Enhancement of fixed-bed flow reactionsunder microwave irradiation by local heating at the vicinal contact points ofcatalyst particles.Sci.Rep.9,222.
[0186] 11.Xie W.,Yang F.,Meng S.,Scarpa F.,Wang L.2020.Perforation ofneedle-punched carbon-carbon composites during high-temperature andhigh-velocity ballistic impacts.Composite Structures 245,112224(2020).
[0187] 12.Ali S.,Garforth A.A.,Harris D.H.,Rawlence D.J.,Uemichi Y.Polymerwaste recycling over“use d”catalysts.Catal.Today 75,247-255(2002).
[0188] 13.De La Puente G.,Klocker C.,Sedran U.Conversion of waste plasticsinto fuels recycling polyethylene in FCC.Appl.Catal.B Environ.36,279-285(2002).
[0189] 14.Lin Y.,Yang M.Catalytic conversion of commingled polymer wasteintochemicals and fuels over spent FCC commercial catalyst in fluidised-bedreactor.Appl.Catal.B Environ.69,145-153(2007).
[0190] 15.Olazar M.,Lopez G.,Amutio M.,Elordi G.,Aguado R.,BilbaoJ.Influence of FCC catalyst steaming on HDPE pyrolysis product distribution.J.Anal.Appl.Pyrol.85,359-365(2009).
[0191] 16.Elordi G.,OIazar M.,Castano P.,Artextxe M.,Bilbao J.Polyethylenecracking on a spent FCC catalyst in a conical spoutedbed.lnd.Eng.Chem.Res.51,14008-14017(2012).
[0192] 17.Eschenbacher A.,Varghese R.J.,Abbas-Abadi M.S.,Van GeemK.M.Maximizing light olefins and aromatics as high value base chemicals viasingle step catalytic conversion of plastic waste.Chem.Eng J 428,132087(2022).
[0193] 18.Moncada Quintero et al.:”lnvestigating mass transfer coefficientsin lean methane combustion reaction through the morphological and geometricanalysis of structured open cell foam catalysts”,Chemical Engineering ScienceVolume 281,5November 2023,119138.
Claims
1. Use of metal-free carbon materials to convert plastics into C2-C4 olefins and / or other hydrocarbons under direct induction heating at a temperature less than or equal to 800°C.
2. Use according to claim 1, wherein the temperature is strictly below 600°C.
3. The use according to claim 1 or 2, wherein the BET surface area of the metal-free carbon material is at least 0.10 m 2 / g and up to 2000m 2 / g, as determined by ASTM-D-3663(2020).
4. Use according to any one of the preceding claims, wherein the carbon of the metal-free carbon material is selected from the group consisting of graphite, graphene, mesoporous carbon, carbon black, acetylene black, pyrolytic carbon, activated carbon and any combination thereof.
5. The use according to any one of the preceding claims, wherein the metal-free carbon material is in a morphology selected from particles, felts such as rolled felts, fibers such as nanofibers, filaments, 2D or 3D fabrics, foams such as open-cell foams, 3D printed structures, spheres, cloths, blocks such as honeycombs, extrudates, rods, bars and particles, tubes such as nanotubes, rings or trilobes, sheets and nanosheets and any combination thereof.
6. Use according to any one of the preceding claims, wherein the metal-free carbon material is supported by a non-carbon structure.
7. A method for converting plastics into C2-C4 olefins and / or other hydrocarbons, comprising: - optionally a step of pre-cracking the plastic, and - A reaction step of passing the metal-free carbon material as defined in any of the preceding claims under direct induction heating at a temperature lower than or equal to 800°C.
8. The process of claim 7, wherein the pre-cracking step, when present, is carried out at a temperature between 300°C and 600°C.
9. The process according to claim 7 or 8, wherein the pre-cleavage step, when present, is carried out under induction heating, Joule heating or microwave heating.
10. A method according to any one of claims 7 to 9, wherein the pre-cracking step, when present, is carried out on silicon carbide, metal beads or any thermally conductive material mixed with the plastic.
11. A method according to any one of claims 7 to 10, wherein in the pre-cracking step, the plastic is pre-cracking in a primary reactor, and the vapor and / or liquid produced in the first part is blown by a gas stream to the material in a secondary reactor, where the cracking process occurs.
12. The use according to any one of claims 1 to 6 or the method according to any one of claims 7 to 11, wherein the plastic is selected from high-density and low-density polyethylene, polypropylene, polystyrene, mixed industrial waste plastics such as low-density polyethylene, PET, PVC and polystyrene containing solid residues, plastics containing solid residues, C 15 -C 45 At least one plastic selected from wax and a polymer distilled at a temperature of 200 to 500°C.
13. The use according to any one of claims 1 to 6 or 12 or the process according to claims 7 to 11, wherein the metal-free carbon material used in the reaction step is not mixed with the plastic material to be converted.
14. Use according to claim 13, wherein the metal-free carbon material is arranged in a packed bed.
15. The use according to any one of claims 1 to 6 or 12 to 14 or the method according to any one of claims 7 to 11, wherein the C2-C4 olefin is at least one selected from ethylene, propylene and butene and dienes produced from ethylene, propylene and butene, and the other hydrocarbon is C 5+ Liquid hydrocarbons and / or gaseous C1 to C4 paraffins.
16. The use according to any one of claims 1 to 6 or 12 to 15 or the method according to any one of claims 7 to 11, wherein the C 5+ Liquid hydrocarbons are fuel oils.